Systematic position of two Pliocene carditids with description of Akardita n. gen. and A. iberica n. sp. (Bivalvia: Carditidae) - Perna, Rafael La; Brunetti, Mauro M.; Bella, Giano Della (Zootaxa, 2018)
Akardita n. gen. is described for a small Pliocene to Recent group of carditids. The type species is Cardita subrevoluta de Stefani, 1888, from the lower Pliocene of Italy. The new genus includes Akardita iberica n. sp., from the lower Pliocene of southern Spain, and Cardita (Venericardia) monodi Nicklès, 1953, an extant species from West Africa. A few additional Neogene species from Europe could turn out to be representatives of the new genus, whose disappearance from European seas seems to be related to an increasing cooling trend during the Neogene–Pleistocene interval. Because of the confused status of carditid taxonomy, about which some observations are reported in the present work, it is not possible to assign the new genus to any of the traditional subfamilies.